2022
DOI: 10.1073/pnas.2115649119
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a poverty reduction intervention on infant brain activity

Abstract: Early childhood poverty is a risk factor for lower school achievement, reduced earnings, and poorer health, and has been associated with differences in brain structure and function. Whether poverty causes differences in neurodevelopment, or is merely associated with factors that cause such differences, remains unclear. Here, we report estimates of the causal impact of a poverty reduction intervention on brain activity in the first year of life. We draw data from a subsample of the Baby’s First Years study, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
95
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(125 citation statements)
references
References 56 publications
6
95
0
2
Order By: Relevance
“…Growing evi dence points to pov erty costs regard ing chil dren's neuro en do crine func tion, early brain devel op ment, and cog ni tive abil ity. Results from a ran dom ized con trol trial showed that reg u lar cash trans fers given to low-income fam i lies increased infant brain activ ity at age 1 (Troller-Renfree et al 2022). Poverty has been found to be asso ci ated with smaller white and cor ti cal gray mat ter and hippo cam pal and amyg dala vol umes in child hood (Luby et al 2013).…”
Section: New Deal and Potential Mechanisms For Human Developmentmentioning
confidence: 99%
“…Growing evi dence points to pov erty costs regard ing chil dren's neuro en do crine func tion, early brain devel op ment, and cog ni tive abil ity. Results from a ran dom ized con trol trial showed that reg u lar cash trans fers given to low-income fam i lies increased infant brain activ ity at age 1 (Troller-Renfree et al 2022). Poverty has been found to be asso ci ated with smaller white and cor ti cal gray mat ter and hippo cam pal and amyg dala vol umes in child hood (Luby et al 2013).…”
Section: New Deal and Potential Mechanisms For Human Developmentmentioning
confidence: 99%
“…SES is also associated with functional connectivity levels for several brain networks, including the default mode network, sensorimotor network, and brain circuits connecting the prefrontal cortex to deeper brain structures like the striatum and amygdala, within the first 6 months of life (Gao et al, 2015;Turesky et al, 2019;Ramphal et al, 2020). Beyond these correlational findings, poverty reduction interventions also suggest a causal role in the associations between SES and brain development (Troller-Renfree et al, 2022). For example, when low-income families were randomly assigned to receive either large or nominal monthly cash gifts shortly after giving birth, infants in the high-cash group exhibited greater EEG power in higher-frequency bands (beta and gamma) compared to infants in the low-cash group a year later, although these differences did not survive multiple comparisons.…”
Section: Introductionmentioning
confidence: 95%
“…Results from the Baby's First Years trial, in which 1000 low-income mothers were randomized to receive either large or nominal monthly cash gifts shortly after delivery, provides experimental evidence that increasing resources for poor mothers improves their children's brain health. 5 Electroencephalographic brain activity at 1 year showed more power in high-frequency bands, a pattern associated with development of subsequent cognitive skills, among infants whose mothers received larger gifts. These changes likely reflect neuroplasticity and environmental adaptation.…”
mentioning
confidence: 96%